2003
DOI: 10.1037/0735-7036.117.3.302
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of handedness for a coordinated bimanual task in chimpanzees (Pan troglodytes), gorillas (Gorilla gorilla) and orangutans (Pongo pygmaeus).

Abstract: Hand preferences for a coordinated bimanual task were assessed in a sample of 31 captive gorillas (Gorilla gorilla) and 19 captive orangutans (Pongo pygmaeus) and were compared with chimpanzee (Pan troglodytes) hand preferences in subjects that were matched on the basis of age, sex, and rearing history. The task required that the apes remove food from the inside edges of a symmetrical polyvinyl chloride pipe presented to them in their home cages. The results indicate significant species differences with chimpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
60
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 46 publications
5
60
1
Order By: Relevance
“…For the less complex tasks, i.e. leading limb (hand or foot), scratching, gesturing and carry/object manipulation, the majority of individuals showed no significant preferences, which supports previous findings (Fagot and Vauclair 1988;Hopkins et al 2003). As predicted by previous research (Fagot and Vauclair 1988;Olson et al 1990), a greater proportion of individuals were significantly lateralised when a more complex behaviour was performed, i.e.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…For the less complex tasks, i.e. leading limb (hand or foot), scratching, gesturing and carry/object manipulation, the majority of individuals showed no significant preferences, which supports previous findings (Fagot and Vauclair 1988;Hopkins et al 2003). As predicted by previous research (Fagot and Vauclair 1988;Olson et al 1990), a greater proportion of individuals were significantly lateralised when a more complex behaviour was performed, i.e.…”
Section: Discussionsupporting
confidence: 89%
“…Fagot and Vauclair (1988) found significant population-level left-hand preferences for feeding tasks that were complex in terms of biomechanical and cognitive demands required. Significant preferences at an individual but not population level have been found for general feeding and for coordinated bimanual feeding tasks (Fagot and Vauclair 1988;Hopkins et al 2003). In contrast other studies have found a lack of population-level preference while feeding (Olson et al 1990;Annett and Annett 1991) and for manipulating food (Olson et al 1990).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, recent studies have documented evidence of population-level behavioral asymmetries in a host of nonhuman vertebrate species (Rogers & Andrew, 2002). With specific reference to primates, there is increasing evidence of population-level handedness in prosimians (Ward, Milliken, & Stafford, 1993), Old and New World monkeys (Hook-Costigan & Rogers, 1997;Spinozzi, Castornina, & Truppa 1998;Vauclair Mequerditchian, & Hopkins, 2005;Westergaard, Kuhn, & Suomi, 1998) and great apes (Hopkins, Stoinski, Lukas, Ross, & Wesley, 2003;Hopkins, Wesley, Izard, Hook, & Schapiro, 2004). Moreover, evidence of population-level neuroanatomical asymmetries have been reported in great apes.…”
Section: Introductionmentioning
confidence: 99%
“…While there is increasing evidence that captive and wild chimpanzees are similar to humans in expressing a tendency towards population-level right-handedness (Hopkins, Stoinski, Lucas, Ross & Wesley, 2003;Hopkins, Wesley, Izard, Hook & Shapiro, 2004;Lonsdorf & Hopkins, 2005) albeit to a lesser degree, the data for capuchins are less clear, with some research groups reporting population-level preferences (e.g., Spinozzi, Castorina, & Truppa, 1998) and others not (e.g., Fragaszy, Fedigan, & Visalberghi, 2004;Westergaard & Suomi, 1996). Individual capuchins do, however, express strong and consistent hand preferences during tasks that require complex bimanual coordination (Fragaszy & Mitchell, 1990;Limongelli, Sonetti, & Visalberghi, 1994;Westergaard & Suomi, 1993a,1993b.…”
Section: Introductionmentioning
confidence: 99%